Rhodium‐Catalyzed Asymmetric Hydroformylation of 1, 1‐Disubstituted Allylphthalimides: A Catalytic Route to β3‐Amino Acids. Issue 4 (22nd February 2013) - Zheng, Xin; Cao, Bonan; Liu, Tang‐lin; Zhang, Xumu
Abstract The high enantioselective rhodium‐catalyzed hydroformylation of 1, 1‐disubstituted allylphthalimides has been developed. By employing chiral ligand 1, 2‐bis[(2S, 5S)‐2, 5‐diphenylphospholano]ethane [(S, S)‐Ph‐BPE], a series of β3‐aminoaldehydes can be prepared with up to 95% enantioselectivity. This asymmetric procedure provides an efficient alternative route to prepare chiral β3‐amino acids and alcohols.